Cultivating river sediments into efficient denitrifying sludge for treating municipal wastewater. Issue 9 (25th September 2019) - Hou, Liangang; Li, Jun; Zheng, Zhaoming; Sun, Qi; Liu, Yitao; Zhang, Kai
Abstract : The river sediment contains a lot of pollutants in many cases, and needs to be treated appropriately for the restoration of water environments. In this study, a novel method was developed to convert river sediment into denitrifying sludge in a sequencing batch reactor (SBR). The river sediment was added into the reactor daily and the hydraulic retention time (HRT) of the reactor was gradually reduced from 8 to 4 h. The reactor achieved in the N O 3   – N removal efficiency of 85% with the N O 3   – N removal rate of 0.27 kg N m −3 d −1 . Response surface analysis represents that nitrate removal was affected mainly by HRT, followed by sediment addition. The denitrifying sludge achieved the highest activity with the following conditions: N O 3   – N 50 mg l −1, HRT 6 h and adding 6 ml river sediments to 1 l wastewater of reactor per day. As a result, the cultivated denitrifying sludge could remove 80% N O 3   – N for real municipal wastewater, and the high-throughput sequence analysis indicated that major denitrifying bacteria genera and the relative abundance in the cultivated denitrifying sludge were Diaphorobacter (33.82%) and Paracoccus (24.49%). The river sediments cultivating method in this report can not only obtain denitrifying sludge, but also make use of sediment resources, which has great application potential.